Bis(mu-quinolin-8-olato)-kappa 3 N,O:O;kappa 3 O:N,O-bis[chloridomethylphenyltin(IV)] - Vafaee, M.; Amini, M.M.; Ng, S.W. (International Union of Crystallography, 2010)
The SnIV atom in the centrosymmetric dinculear title compound, [Sn(2)(CH(3))(2)(C(6)H(5))(2)(C(9)H(6)NO)(2)Cl(2)], shows a trans-C(2)SnNO(2)Cl distorted octahedral coordination [C-Sn-C = 157.83 (8)degrees]. The quinolin-8-olate anion chelates to the Sn atom; its O atom also binds to the inversion-related Sn atom, forming the dinuclear compound. In the crystal structure, weak intermolecular C-H...Cl hydrogen bonding links the molecules, forming supramolecular chains running along [100].